Performance analysis of a fabricated line focusing concentrated solar distillation system - Larik, Temoor Abbas; Jakhrani, Abdul Qayoom; Jatoi, Abdul Rehman; Mukwana, Kishan Chand (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
A line focusing concentrated solar distillation unit was developed and its techno-economic analysis was carried out using batch flow, continuous flow without and with tracking mechanisms. Physical quality parameters of feed and distilled water samples, water temperature at different points, performance analysis and estimated production of developed unit were examined. The examined quality parameters of distilled water were well below permissible limits. The water temperature inside the concentrated tube was in the range of 107.0ËšC to 109.0ËšC. The quantity of distilled water was observed to be inversely proportional to the amount of total dissolved solids in the water samples. The measured average daily and estimated lifetime yield from the developed unit during batch flow was 4.0 and 13,621.0 liters, for continuous flow without tracking 5.1 and 19,689.0 liters, and with tracking mechanism 5.7 and 21,758.0 liters, respectively. The continuous flow with tracking mechanism was found as best method for the production of distilled water. The total life cycle cost of the project was estimated to be PKR 62,144.00. The estimated unit cost of the distilled water per liter would be PKR 6.06 for continuous flow with tracking and PKR 9.69 for batch flow technique. Â©2019. CBIORE-IJRED. All rights reserved